2012
DOI: 10.1007/s11999-011-2034-4
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Technique: When to Arthroscopically Repair the Torn Posterior Cruciate Ligament

Abstract: Background Posterior cruciate ligament injuries can occur as isolated ligament ruptures or in association with the multiligament-injured knee. Delayed reconstruction, at 2-3 weeks post-injury, is predominantly recommended for posterior cruciate ligament tears in the multiligamentinjured knee. While acute bone and soft tissue avulsion patterns of injury can be amenable to repair, the described techniques have been associated with some difficulties attaching the avulsed ligament.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 34 publications
0
35
0
Order By: Relevance
“…If surgery is delayed, it is inevitable that the PCL will be treated with autograft or allograft reconstruction, as delay results in obscuration of tissue planes and loss of tissue integrity with ligament retraction. 1,[6][7][8][9] However, if early surgical intervention is planned (within 3 weeks from the time of injury) then primary repair of the PCL can be achieved [10][11][12] and has demonstrated positive clinical outcomes comparable with reconstruction. 13,14 In MLKI, PCL disruption occurs most frequently at the femoral insertion or midsubstance of the ligament, although distal injury typically involves an attached osseous fragment related to either avulsion or coexistent tibial plateau fracture.…”
Section: Introductionmentioning
confidence: 99%
“…If surgery is delayed, it is inevitable that the PCL will be treated with autograft or allograft reconstruction, as delay results in obscuration of tissue planes and loss of tissue integrity with ligament retraction. 1,[6][7][8][9] However, if early surgical intervention is planned (within 3 weeks from the time of injury) then primary repair of the PCL can be achieved [10][11][12] and has demonstrated positive clinical outcomes comparable with reconstruction. 13,14 In MLKI, PCL disruption occurs most frequently at the femoral insertion or midsubstance of the ligament, although distal injury typically involves an attached osseous fragment related to either avulsion or coexistent tibial plateau fracture.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Difelice et al 9 in 2012 reported on 3 patients with PCL peel-off injuries; they performed a PCL repair passing Bunnell-type stitches into the substance of the ligament and then passed the sutures through drill holes into the femoral footprint and tied them over a bony bridge.…”
Section: Discussionmentioning
confidence: 99%
“…3 Arthroscopic repair of femoral avulsion and peel-off lesions of the PCL has been reported. [4][5][6][7][8][9] In most of these articles, a transosseous repair with sutures passed through 2 bone tunnels into the medial femoral condyle was described.…”
mentioning
confidence: 99%
“…Schenck et al [28] found that midsubstance tears occur at a low strain rate and avulsion ''stripping'' injuries from the femoral side occur at a high strain rate in hyperextension in a cadaveric knee. In several reports, avulsion of the PCL was called a ''peel off lesion'' that occurs through Sharpey's fibers and can have small fragments of bone attached to the PCL [7,10,25]. Patients 1 through 3 (Table 1) may be considered to have massive peel off lesions.…”
Section: Discussionmentioning
confidence: 99%